A Preliminary Exploration of the Multimedia Principle’s Applicability for Improving Comprehension of Youth Interrogation Rights - Lively, Christopher J. (Criminal justice and behavior, 2023)
We examined the extent to which presenting youth interrogation rights using different combinations of three multimedia elements (Animation, Audio, and Caption) improved comprehension. A 2 (Animation: Present, Absent) × 2 (Audio: Present, Absent) × 2 (Caption: Present, Absent) between-participants design was employed using samples of adults (Experiment 1: N = 207) and youth (Experiment 2: N = 193). Participants in both experiments were shown one of eight multimedia presentations and asked about their understanding of the presented youth interrogation rights. In both experiments, the multimedia presentation that contained animation and caption led to the highest level of comprehension. Implications of these findings for protecting youth and the use of technology during interrogations are discussed.